Delmira Agustini: canon y subversión = Delmira Agustini: canon and subversion - Fernández dos Santos, Mirta (2017)
In the poetic work of Delmira Agustini, it can be seen the heartbreaking stress between the patriarchal and the marginal position to the women that writes. Agustini felt the dualism among the conventions and the literary models suggested from a perspective traditionally masculine and her lyric subjectivity, consideringthat the feminine images had always constitute the aesthetic subject (the other) and no the subject (I) of the poetic text. Agustini hides herself behind a series of feminine masks that they change throughout the artistic and vital trajectory, in order to minimize the ravaged of «the anxiety of the influence» that they are intensifiedby «the anxiety of the authority».